EVALUASI PENGGUNAAN SISTEM E-FILING LOADER E-SPT ATAS PPh BADAN SEBAGAI UPAYA PENGENDALIAN INTERNAL DI KPP PRATAMA MEDAN POLONIA - Siregar, Oktarini Khamilah; Aulia, Nurul (Universitas Pembangunan Panca Budi, 2025)
Online reporting system in tax reporting implemented by the Directorate General of Taxation automatically provides convenience options for taxpayers who have a busy schedule but want to report their Annual Notification anywhere without the need to queue to spend a long time in an integrated service place. The e-filing loader e-spt for Corporate Income Tax at the Medan Polonia Primary Tax Service Office is expected to assist internal parties in achieving the expected targets through its system. The purpose of this study is to evaluate the e-filing loader e-spt system of the Corporate Income Tax whether it can help in internal control efforts through system planning criteria, the system implementation process, the use of the system, and the benefits and objectives of the system. Based on the evaluation that I have done through the Interview system related to predetermined criteria, it shows that the use of the E-filing loader e-spt system for Corporate Income Tax is sufficient to assist the tax authorities in collecting Annual Notification Notification as an internal control effort at the Medan Polonia Primary Tax Service Office.